Feasibility of a Pharmacy-Based Influenza Immunization Program in an Academic Emergency Department. (November 2013) - Cohen, Victor; Jellinek-Cohen, Samantha P.; Likourezos, Antonios; Lum, Diane; Zimmerman, David E.; Willner, Marc A.; Rose, Jonathan; Marshall, John P.
Background: From September 2002 to August 2010, 13 patients who were discharged from the emergency department (ED) were immunized against influenza. This correlates with a time when pharmacists were not permitted to vaccinate patients in New York.Objective: The objectives of this study were to determine the feasibility of a pharmacist-based influenza vaccination program in the ED, assess patients' willingness to be vaccinated by a pharmacist, and identify reasons for declination.Methods: This was a cross-sectional study involving English-speaking patients older than 18 years. The pharmacist vaccinated patients, if they consented. Patients who refused to be vaccinated were asked why they did not want to receive the vaccine and their perception of pharmacists vaccinating patients in the ED. The percentage of patients vaccinated; time elements associated with the process of screening, counseling, and vaccinating; and the type and frequency of adverse events were recorded.Results: Of 149 patients, 62 patients (41%) agreed to receive the vaccine, a 4-fold increase from the previous 8 years. The median screening and vaccination time was 8 minutes. Of those not receiving a vaccine in the ED, 74% were willing to receive the influenza vaccine from a pharmacist, and 78% were willing to receive the vaccine in the ED. The most common reason for refusal was perception of low self-risk (43.9%). No adverse events were reported.Conclusions: A pharmacist-based influenza immunization program is feasible in the ED and has the potential to successfully and safely increase the percentage of adult patients receiving the vaccine.